Interactive qualitative analysis a systems method for qualitative research - Northcutt Norvell; McCoy Danny (London Sage, 2004)
This book does an excellent job of integrating design, methods, and analysis. aims to help students unscramble the mysteries of qualitative data collection, coding, and analysis by showing how to use a systematic, qualitative technique: interactive quali
Accompanies a CD-ROM bearing acc no D690
Keywords: Qualitative research